Kontribusi Amal Usaha Pendidikan Muhammadiyah terhadap Pembangunan Sumber Daya Manusia - Mutiarani, Yuliana; Safitri, Assha Kamila; Mardiana, Dina (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Human resource development has become a strategic agenda for Indonesia in facing social, economic, and technological transformation toward Golden Indonesia 2045. Community-based education plays an important role because it can expand access, shape character, and strengthen students’ social capacity. This study aims to analyze the contribution of Muhammadiyah’s educational charitable enterprises to human resource development in Indonesia. This study employed a descriptive qualitative approach using literature study and document analysis methods. The research population consisted of all documents, official reports, and scientific publications discussing Muhammadiyah education, modern Islamic education, and human resource development. The sampling technique used was purposive sampling, with samples consisting of official Muhammadiyah documents, reputable journal articles, academic books, and national education policy documents relevant to the research focus. The research location covered Muhammadiyah’s educational charitable enterprises in Indonesia as a national institutional object of study. The data were analyzed using qualitative content analysis and thematic analysis through the processes of data condensation, data display, and conclusion drawing. The findings show that Muhammadiyah’s educational charitable enterprises contribute to human resource development through expanding educational access, improving learning quality, shaping moderate character, developing leadership, and strengthening work readiness and entrepreneurship. This study implies the importance of strengthening collaboration between the government and Muhammadiyah in expanding educational equity, improving learning quality, and shaping a knowledgeable, character-based, adaptive, and competitive generation.